Assessments of Prevalence of Ponticulus Posticus, Atlas Posterior Arch Deficiency, Sella Turcica Bridging, Maxillary Canine Impaction, and Associations Among Them in 500 CBCTs of Italian Orthodontic Patients - Macrì, Monica; Perrella, Giada; Varvara, Giuseppe; Murmura, Giovanna; Traini, Tonino; Rendina, Fabiola; Festa, Felice (Frontiers in Dental Medicine, 2021)
Background: Objective: The ponticulus posticus (PP) is an important anomaly of the atlas, (C1 vertebra) with a complete or partial bone bridge that transforms the groove of the vertebral artery (VA) into a canal (arcuate foramen). The aim was to retrospectively determine PP prevalence evaluating morphological features and the possible association with other dentoskeletal anomalies in the mid-face and neck area such as maxillary canine impaction (MCI), atlas posterior arch deficiency (APAD), sella turcica bridging (SB). The aim of this study was to determine ponticulus posticus (PP) prevalence and morphologic features. Methods: The study was conducted in the Department of Medical, Oral and Biotechnological Sciences of the University “G. D'Annunzio” in Chieti. The detection of PP was performed on 500 CBCT images of patients (6 to 87 year). The sample included 500 Italian patients’ CBCT (age range: 6–87), 202 males (40.4%) and 298 (59.6%) females who presented for orthodontic diagnosis and treatment planning. Results: Analysis revealed the presence of uni- and bilateral ponticulus posticus in 110 patients (22%): 24 (4.8%) bilateral complete PP, 12 (2.4%) complete PP on the left, 6 (1.2%) complete PP on the right, 8 (1.6%) complete PP on the right and partial PP on the left, 6 (1.2%) complete PP on the left and partial PP on the right, 26 (5.2%) partial bilateral PP, 18 (3.6%) partial left PP and 10 (2%) partial PP on the right. Chi-square statistics confirmed that there are significant associations between MIC and PP (P = 0.020) and between SB and MIC (P > 0.00001). No correlation between chronological age and PP presence (P = 0.982), between chronological age and PP morphotypes (P = 0.779), between APAD and PP (P = 0.0757), between SB and PP (P = 0.111), between APAD and MIC (P = 0. 222) were found. Conclusion: This observational study showed how bilateral partial variant and bilateral complete variant are the most represented morphotypes in all age groups. The prevalence of MIC is positively associated with PP and with SB.